The transition of polarized dust thermal emission from the protostellar envelope to the disc scale. Issue 1 (23rd July 2021) - Lam, Ka Ho; Chen, Che-Yu; Li, Zhi-Yun; Yang, Haifeng; Cox, Erin G; Looney, Leslie W; Stephens, Ian
ABSTRACT: Polarized dust continuum emission has been observed with Atacama Large Millimeter/submillimeter Array in an increasing number of deeply embedded protostellar systems. It generally shows a sharp transition going from the protostellar envelope to the disc scale, with the polarization fraction typically dropping from 5 per cent to 1 per cent and the inferred magnetic field orientations becoming more aligned with the major axis of the system. We quantitatively investigate these observational trends using a sample of protostars in the Perseus molecular cloud and compare these features with a non-ideal magnetohydrodynamic disc formation simulation. We find that the gas density increases faster than the magnetic field strength in the transition from the envelope to the disc scale, which makes it more difficult to magnetically align the grains on the disc scale. Specifically, to produce the observed 1 per cent polarization at 100 au scale via grains aligned with the B-field, even relatively small grains of 1 μ m in size need to have their magnetic susceptibilities significantly enhanced (by a factor of ∼20) over the standard value, potentially through superparamagnetic inclusions. This requirement is more stringent for larger grains, with the enhancement factor increasing linearly with the grain size, reaching ∼2 × 10 4 for millimetre-sized grains. Even if the required enhancement can be achieved, the resulting inferred magnetic field orientation in the simulation does not show a preference for the major axis, which is inconsistent with the observed pattern. We thus conclude that the observed trends are best described by the model where the polarization on the envelope scale is dominated by magnetically aligned grains and that on the disc scale by scattering.